Antibacterial and Antibiofilm Activity of Temporin-GHc and Temporin-GHd Against Cariogenic Bacteria, Streptococcus mutans - Zhong, Hengren; Xie, Zhipeng; Wei, Hanqi; Zhang, Shuxia; Song, Yanting; Wang, Manchuriga; Zhang, Yingxia (Frontiers in Microbiology, 2019)
Temporin-GHc (GHc) and temporin-GHd (GHd) produced by the frog Hylarana guentheri, had shown broad-spectrum antibacterial activities against bacteria and fungi. In this study, we investigated whether they exert antibacterial and antibiofilm activities against cariogenic bacteria, Streptococcus mutans. GHc and GHd adopt the random coil conformation in aqueous solution, and convert to α-helix in membrane mimetic environments by using circular dichroism spectroscope. They are positively charged by histidine, with the polar and nonpolar amino acids on opposing faces along the helix. The amphipathicity enabled the peptides to target at bacterial membrane, leading to an increase in membrane permeation and disruption of S. mutans, which allowed the peptides to bind with genomic DNA. GHc and GHd completely impeded the initial attachment of biofilm formation and disrupted preformed S. mutans biofilms. The expression of exopolysaccharide (EPS) biosynthesis genes which synthesize glucosyltransferases in S. mutans was downregulated by exposing to GHc or GHd, contributing to the decrease of soluble and insoluble EPS. GHc and GHd exhibited selectivity toward S. mutans in the presence of human erythrocytes, and no cytotoxicity toward human oral epithelial cells was observed at a concentration of 200 μM. These results laid the foundation for the development of GHc and GHd as potential anti-caries agents.